NEW APPROACHES IN NUCLEAR ENERGY: THORIUM AND USE OF ENERGY RESOURCE - Erol KAPLUHAN; - (International Journal of Eurasia Social Sciences, 2015)
Energy is the leading condition of economic activity in all countries, developed and developing. Us to meet our energy needs domestic production rate has declined steadily in the 2000s. The importance of energy in the next year will increase day by day. They should try all ways to reduce dependence on foreign energy and research done in this direction should be accelerated. Endangered fossil resources as an alternative to the energy needs of the growing emphasis on new sources of energy should be focused on the supply from other sources. To meet the growing energy needs of our country lacking fossil energy sources lignite excluding nuclear energy, it has been one of the alternative energy sources.Uranium is used in nuclear power plants throughout the world for decades. Still it continues to be used in the same way. However, in recent years it should be a mine can run either in general more powerful energy sources with the need for the world sought several new mines are needed for new energy sources. Thorium is an element, which can be used in nuclear power plants to generate electricity. Today, as a resource to respond to this need it is projected thorium mine.. However, due to lack of thorium mine yet have the knowledge and technology to use in nuclear power plants people literally can not be fully evaluated. Research and studies thorium is proved to be the energy source of the future.